Intimate partner violence and utilization of reproductive and maternal health services in Cambodia - Vanthy Mai; Win Ei Phyu (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The purpose of this paper is to explore an association between women experience lifetime intimate partner violence (IPV) and women decision making with utilization of reproductive and maternal health services in Cambodia. Design/methodology/approach - An analysis of secondary data of Cambodia Demographic and Health Survey (CDHS) 2014. The total number of sample size was 1,539 married women who had birth in the last five years prior to the time of interview and completed the domestic violence module in the CDHS 2014 questionnaire. χ² test and binary logistic regression were performed in this study. Findings - Results give an evidence that emotional violence had significant impact on receiving sufficient antenatal care (ANC) (OR: 0.7, 95%CI: 0.43-0.86) while physical violence had significant association with deliver with skilled birth attendance (SBA) (OR: 0.5, 95%CI: 0.27-0.79). Further, women's participation in household decision making played as important factor in enabling women revive sufficient ANC (OR: 1.7, 95%CI: 1.19-2.29), and utilization of modern contraceptive method (OR: 1.5, 95%CI: 1.09-1.97). Originality/value - This study provides significant finding on the impact of IPV and women's decision making on reproductive and maternal health in Cambodia. Result has drawn an attention to policy makers, related ministries and stakeholder to promulgate and effectiveness of policies and program implementation within the country.